(untitled) (Research, Society and Development, 2022)
Cowpea is part of the diet, especially for the population of the North and Northeast regions of Brazil. However, this region has the lowest productivity rates, a result, among other factors, of inadequate management of soil correction and fertilization techniques. Vegetable ash appears to be a promising organic source for the correction and fertilization of agricultural soils. The objective of this work was to analyze the efficiency of vegetable ash in the development and production of cowpea in the semi-arid region of Piauí. For this, a completely randomized design was adopted with five treatments (0; 25; 50; 200 and 300% of the recommended dose) and five replications. Soil and ash analysis were performed and both were incorporated into 8 dm³ pots and incubated for a period of 30 days. Subsequently, sowing was carried out at a depth of 0.02 m, with a density of three seeds per pot. Seven days after germination, thinning was performed, leaving one plant per pot. At harvest, the following variables were evaluated: plant height, stem diameter, number of leaves, number of grains, aerial part fresh mass, aerial part dry mass, root length, root volume, number of pods per plant, average pod length and yield. The application of vegetable ash improved the development and productivity of cowpea, where the dose of 874.63 kg ha-1 promoted the highest productivity (2528.50 kg ha-1). However, at doses above the recommended, there was a reduction in the development of the culture.